Assessing tradeoffs in the design of climate change adaptation strategies for water utilities in Chile. (15th January 2022) - Ricalde, Iñigo; Vicuña, Sebastián; Melo, Oscar; Tomlinson, James E.; Harou, Julien J.; Characklis, Greg
Abstract: Climate change is a challenge to drinking water providers worldwide and to regulatory frameworks that consider long-term investment decisions. Coping with an unstable climate warrants adjustments in regulations and new investments. The investment required to maintain a selected service level needs to balance the potential for high regret stranded assets with the political and socioeconomic consequences of not meeting water demands. In recent years, the City of Santiago in Chile has seen drought events associated with climate change, which could worsen in the future. Chile's drinking water regulatory framework does not account for uncertainty in infrastructure design to cope with the potential impacts of such events. This work presents an adaptation option design process that considers multiple plausible climate change-impacted future scenarios, accommodating both structural and nonstructural measures. In our Santiago case study adaptation measures include extensions to the existing Chilean water market and traditional structural alternatives (e.g., storage infrastructure); all are represented in a simulation model of the water utility. We evaluate and optimize packages of efficient adaptation measures for various climate scenarios. This allows comparing different portfolios of combined institutional and infrastructure interventions via a range of stakeholder measures and comparing their tradeoffs under different plausible climate-impacted hydrological scenarios. Results showed that water supply performance without climate change adaptation is worse under climate scenarios with lower water availability, which are likely to be associated with higher GHG emission scenarios such as RCP 8.5. The optimized portfolios implement various combinations of adaptation strategies to reduce the impacts of this poor performance. Considering the uncertainty on future climate scenarios, the use of nonstructural adaptation measures such as option contracts exhibits the advantage of providing water in critical periods while avoiding large investments such as building reservoirs or the purchase of permanent water rights, which could end up underused if favorable climate scenarios manifest. Highlights: Adaptation could reduce climate change impacts on Santiago's water supply system. In such adaptation there are trade offs between financial costs and system resilience. Combined portfolios of strategies can accommodate a range of stakeholder objectives. Water markets provides flexible adaptation strategies when planning under uncertainty.